The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5099/aj140200128
|View full text |Cite
|
Sign up to set email alerts
|

UTL-5g Lowers Elevated Blood Levels of TNF-a and TGF-? and Increases Survival Rates in Animals Treated with LPS/D-(+)-galactosamine

Abstract: N-(2,4-dichlorophenyl)-5-methyl-1,2-oxazole-3-carboxamide (UTL-5g) is a small-molecule chemoprotector against cisplatin and radioprotector against radiation. To further investigate its protective effects, we evaluated whether UTL-5g protects mice in a septic shock animal model. The two metabolites of UTL-5g, 5-methylisoxazole-3-carboxylic acid (Isox) and 2,4-dichloroaniline (DCA) were also evaluated side-by-side with UTL-5g. First, mice were pretreated with UTL-5g, Isox, and DCA before the i.p. injection of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Further studies confirmed that UTL-5g was a prodrug that required metabolic activation to form the active metabolite 5-methylisoxazole-3-carboxylic acid (ISOX) to exert chemo-and radioprotective activity (Zhang et al, 2014). The hydrolytic conversion of UTL-5g to ISOX and 2,4-dichloroaniline (DCA) (Fig.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Further studies confirmed that UTL-5g was a prodrug that required metabolic activation to form the active metabolite 5-methylisoxazole-3-carboxylic acid (ISOX) to exert chemo-and radioprotective activity (Zhang et al, 2014). The hydrolytic conversion of UTL-5g to ISOX and 2,4-dichloroaniline (DCA) (Fig.…”
mentioning
confidence: 75%
“…1), the active metabolite that exerts chemo-and radioprotective activity (Zhang et al, 2014). UTL-5g hydrolysis to equal molars of ISOX and DCA in HLM was NADPH-independent (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Both Isox and DCA from the treatment of UTL-5g by human microsome were further confirmed by LC-MS/MS [7]. Furthermore, a recent study showed that UTL-5g is both an active drug and a prodrug with Isox as the active metabolite [8]; however, UTL-5g is very quickly converted into Isox in human plasma [7]. Therefore it is of interest to investigate whether Isox by itself could be a viable drug candidate.…”
Section: Introductionmentioning
confidence: 86%
“…For example, UTL-5g reduces cisplatin-induced toxicity by protecting kidney, liver, and platelets, thereby increasing the tolerance of mice for cisplatin (Shaw et al, 2013). UTL-5g increases the survival rates of mice treated with lipopolysaccharide (LPS) (Zhang et al, 2014) and reduces radiation-induced liver damage (Shaw et al, 2012). Given the critical role for macrophages in inflammation we hypothesized that UTL-5g exerts a primary anti-inflammatory effect in vivo by suppressing macrophage activation.…”
Section: Introductionmentioning
confidence: 99%